Pendampingan Mitigasi Bencana Gempa Bumi dan Tsunami Berbasis Pengetahuan Lokal pada Masyarakat Rentan Bencana di Kabupaten Mukomuko Bengkulu - Dian Agustina; Etis Sunandi; Sigit Nugroho (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The first objective of this activity is to increase knowledge and understanding of the rescue procedures, evacuation routes, and emergency response plans when a large earthquake occurs. The second objective is to increase the knowledge and ability to mobilize available resources. With this knowledge and capability, the community can choose and sort out the resources that must be prioritized, so that losses can be reduced as little as possible. Referring to the results of the study, reducing the impact of earthquake and tsunami disaster risk is greatly influenced by emergency response plan factors, disaster warning system factors, knowledge factors, policy and guidance factors, and the ability of team mobilization. The conclusion obtained from the results of this activity is that the Air Rami Sub-district community gained increased knowledge and understanding of earthquake and tsunami mitigation. This can be seen from the enthusiasm of stakeholders and the public in participating in socialization activities. It is also supported by the Wilcoxon statistical test, the result showed that socialization increases public knowledge in understanding disaster mitigation, especially earthquakes and tsunamis.